MATERNAL SENSITIVITY AND LATENCY TO POSITIVE EMOTION FOLLOWING CHALLENGE: PATHWAYS THROUGH EFFORTFUL CONTROL. Issue 3 (26th March 2014) - Conway, Anne; Mcdonough, Susan C.; Mackenzie, Michael; Miller, Alison; Dayton, Carolyn; Rosenblum, Katherine; Muzik, Maria; Sameroff, Arnold
ABSTRACT The ability to self‐generate positive emotions is an important component of emotion regulation. In this study, we focus on children's latency to express positive emotions following challenging situations and assess whether this ability operates through early maternal sensitivity and children's effortful control. Longitudinal relations between maternal sensitivity, infant negative affect, effortful control, and latency to positive emotion following challenge were examined in 156 children who were 33 months of age. Structural equation models supported the hypothesis that maternal sensitivity during infancy predicted better effortful control and, in turn, shorter latencies to positive emotions following challenge at 33 months. Directions for future research are discussed.